Intergenerational Transmission of Welfare Benefit Receipt: Evidence from Germany - Regina T. Riphahn; Jennifer Feichtmayer (Review of Income and Wealth, 2024)
We study the intergenerational transmission of welfare benefit receipt in Germany. We first describe the correlation between welfare receipt experienced in the parental household and subsequent own welfare receipt of young adults. In a second step, we investigate whether the observed correlations reflect causal effects of past welfare experience. We use family fixed effects estimations and Gottschalk's (1996) approach and take advantage of the long-running German Socio-Economic Panel Survey to contribute to a sparse literature. We find strong positive correlations between parental and own welfare receipt. These patterns do, however, not persist after controlling for unobserved heterogeneities. Therefore, our results suggest that the strong intergenerational correlation of welfare benefit receipt is determined by family background rather than by the experience of parental welfare benefit receipt.
Keywords: 330; causal effect; family fixed effects; Gottschalk estimator; intergenerational mobility; social assistance; welfare